Metodología para la gestión de proyectos en Intelcost S.A.S. (2022)
Intelcost SAS is a company incorporated in 2015, aimed at large buyers, which offers an integrated system to manage purchases in a strategic way leveraged in technology and at the best price. The growth of Intelcost in the last year has been more than 100%, regarding of installed capacity, human resources and the sale of services through the distribution of software. For those reasons, the need to structure and standardize the processes associated with the management of the different projects to be developed by the company, with the aim of maximizing the resources available in the company, unifying criteria in the management of the projects, and solving the problems current associated with the lack of standardization of processes, failures in planning and the problems that occur daily in the execution of projects. At the time of the initial assessment, there was no budget control process of the projects and the procedures associated with the management of the projects were not defined. Our proposal, was to develop a methodological guide for the management of projects from the point of view of all the processes: Initiation, Planning, Execution and Monitoring and Closing; based on the principles of agile methodologies and the guidelines of the PMBOK in a way that will adjust to the needs, organizational structure and types of business that are developed in Intelcost.